2011
DOI: 10.5539/gjhs.v3n2p134
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Upper Trapezius Latent Myofascial Trigger Points on Neck Pain and Disability

Abstract: Purpose: To compare neck pain and disability between people with and without latent myofascial trigger points (MTrP) in Upper Trapezius. Methods: The participants of the study were asked to fill the Northwick Park Neck Pain Questionnaire (NPNQ) following which bilateral upper trapezius muscles were assessed for the presence of latent MTrP. The participants were placed into two groups; an experimental group who had latent MTrP in upper trapezius and a control group who did not have trigger points. Twenty seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…The results of this study did not show a significant difference between the range of motion of extension and right and left lateral flexion in the healthy subjects and subjects with HTPs group, which is different from the results of previous studies in this issue (31,44,46), which is probably due to the different methods and tools used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study did not show a significant difference between the range of motion of extension and right and left lateral flexion in the healthy subjects and subjects with HTPs group, which is different from the results of previous studies in this issue (31,44,46), which is probably due to the different methods and tools used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no available study to the researches that investigated the sense of force in these subjects, with which the results of the present study can be compared. Researchers reported that the presence of TPs may increase pain and inflammation(42)(43)(44)(45). Also, Proske et al and Weerakkody et al observed a relationship between pain and increased error of sense of force(13,23).…”
mentioning
confidence: 99%